Significant differences in intestinal fungal community of hooded cranes along the wintering periods - Wu, Yuannuo; Li, Zihan; Zhao, Jingru; Chen, Zhong; Xiang, Xingjia (Frontiers in Microbiology, 2022)
The intestinal microbiota play vital roles for health of wild birds in many ways. Migratory birds with unique life history might increase the risk of pathogenic transmission across the regions. However, few studies have clarified the fungal community structure and inferred the potential pathogens in guts of migratory birds. The high-throughput sequencing method was applied to analyze the fungal community structure and detect the potential fungal pathogens in guts of hooded cranes among different wintering stages. Significant differences were found in gut fungal community composition of hooded cranes among three wintering stages, with the lowest fungal diversity in the late wintering stage. In the late stage, hooded cranes harbored higher relative abundance of plant saprotroph, contributing to food digestion for hosts. Hooded cranes were associated with the lowest diversity and relative abundance of animal pathogens in the late wintering stage. There was an increasing trend of deterministic process for gut fungal community assembly, suggesting that hosts interaction with their fungal communities changed by enhanced gut selection/filtering along wintering periods. Hooded crane was associated with the strongest gut selection/filtering to obtain defined gut fungal community with retaining probiotics (i.e., plant saprotroph) and exclusion of certain pathogens in the late wintering stage. Overall, these results demonstrated that hooded cranes might regulate their gut microbiota to enhance digestion and decrease gut pathogens in preparation for long-term migration.